Some properties for a subclass of BazileviÄ functions* - S, Abdul Halim, (Malaysian Journal of Science, 2001)
Let S represents the class of functions Æ’ which are analytic and univalent in the unit disc D = z:|z|< 1 with Æ’(z) =z+âˆ‘(n=2)^âˆžan.z^n We denote B to be the class of BazileviÄ functions which to date forms the largest subclass of S. ln this paper we introduce the class B(Î±,Î²), a subclass of B and give some interesting properties for this class, in particular results concerning iterated integral operators.